Autobiography of Malcolm X - Thomas, Jalen; Haley, Alex. ([Not indicated] : Babelcube Inc., 2019)
The controversial leader of the Black Muslims tells the story of his life and his part in the civil rights movement.
Introduction -- Nightmare -- Mascot -- "Homeboy" -- Laura -- Harlemite -- Detroit Red -- Hustler -- Trapped -- Caught -- Satan -- Saved -- Savior -- Minister Malcolm X -- Black Muslims -- Icarus -- Out -- Mecca -- El-Hajj Malik El-Shabazz -- 1965 -- Alex Haley : epilogue -- Ossie Davis : on Malcolm X.
Keywords: X, Malcolm, -- 1925-1965.; Malcolm X -- Biography; Black Muslims -- Biographies; Biographies